Central Administration of Insulin and Leptin Together Enhance Renal Sympathetic Nerve Activity and Fos Production in the Arcuate Nucleus - Habeeballah, Hamza; Alsuhaymi, Naif; Stebbing, Martin J.; Jenkins, Trisha A.; Badoer, Emilio (Frontiers in Physiology, 2017)
There is considerable interest in the central actions of insulin and leptin. Both induce sympatho-excitation. This study (i) investigated whether centrally administered leptin and insulin together elicits greater increases in renal sympathetic nerve activity (RSNA), mean arterial pressure (MAP) and heart rate (HR) than when given alone, and (ii) quantified the number of activated neurons in brain regions influencing SNA, to identify potential central sites of interaction. In anesthetised (urethane 1.4-1.6 g/kg iv) male Sprague-Dawley rats, RSNA, MAP and HR were recorded following intracerebroventricular (ICV) saline (control; n=5), leptin (7 μg; n=5), insulin (500 mU; n=4) and the combination of leptin and insulin; (n=4). Following leptin or insulin alone, RSNA was significantly increased (74% and 62% respectively). MAP responses were not significantly different between the groups. Insulin alone significantly increased HR. Leptin alone also increased HR but it was significantly less than following insulin alone (P<0.005). When leptin and insulin were combined, the RSNA increase (124%) was significantly greater than the response to either alone. There were no differences between the groups in MAP responses, however, the increase in HR induced by insulin was attenuated by leptin. Of the brain regions examined, only in the arcuate nucleus did leptin and insulin together increase the number of Fos-positive cell nuclei significantly more than leptin or insulin alone. In the lamina terminalis and rostroventrolateral medulla, leptin and insulin together increased Fos, but the effect was not greater than leptin alone. The results suggest that when central leptin and insulin levels are elevated, the sympatho-excitatory response in RSNA will be greater. The arcuate nucleus may be a common site of cardiovascular integration.